Mitral Valve Surgery by Right Minithoracotomy Vs Traditional Median Full Sternotomy - Khan, Muhammad Aamir; Ahmed, Tahseen; Shaukat, Nausheen; Janjua, Asif Mahmood; Iqbal, Muhammad Afsheen; Hasan Kirmani, Syed Muzaffir; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the clinical outcomes of mitral valve surgery through right minithoracotomy versus median full sternotomy. Study Design: It was a comparative cross-sectional studyPlace and Duration of Study: Carried out at the Armed Forces Institute of Cardiology/National Institute of Heart Diseases(AFIC/ NIHD). Data was gathered from hospital database from Dec 2013 to Mar 2020.Methodology: From December 2013 to March 2020, 721 patients with various mitral valve diseases were treated at our institute with isolated mitral valve surgery. 50 patients had (MIMVS). 670 patients, on the other hand, underwent conventional median full sternotomy (MFS) mitral valve surgery. We selected 50 MFS patients with similar age, gender, Euro Score, NYHA functional class, Left ventricular ejection fraction (LVEF), mitral valve disease grade, renal and liver function. The outcome variables chosen for this study were cross clamp time (CXT), cardio pulmonary bypass (CPB) time, intensive care unit (ICU) stay, postoperative pain, and Length of stay (LOS).Results: The majority (n=42, 84%) of MIMVS group patients had CPB time between 122-201 minutes, whereas, majority (n=33,66%) of MFS group had CPB time between 81-134 minutes. In MIMVS group maximum number of the patients (n=36,72%)had ICU stay of 50-70 hours duration, whereas, in MFS group, maximum number of patients (n=40,80%) stayed in ICU for 10-30 hours duration. The mean CX time for MFS approach was 72.08 minutes while that for MIMVS was 96.9 minutes. Similarly,the median and mode for MFS were 68.5 minutes and 47 minutes respectively. Pain after surgery plus subsequent overall hospital length of stay (LOS) were reduced in MIMVS group.Conclusions: MIMVS is related with elevated CPB and CXT, which subsequently resulted in longer ICU stay while reduced post-operative pain lead to decrease in overall hospital length of stay.